PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGHETHER (NHT) UNTUK MENINGKATKANT HASIL BELAJAR IPASISWA KELAS V SEKOLAH DASAR NEGERI 001 SEBERIDA KECAMATAN BATANG GANSAL - Lestari, Eko Puji; Alpusari, Mahmud; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on preliminary observation in SDN 001 Seberida pound problems in Learning in class V. Teacher Centered Learning by Process, Learning models used by teacher have not varied and monotonous. The Teacher has not tought students in group. The students do not perform the activity and tend to be rowdy group at the time of the learning take place. So the impact on students learning outcomes are lower with classical completeness 52 % below the KKM. Based on the chosen solution to these problems is to impements Cooperative Learning ( NHT) because this model is a model of group Learning with a number of head that can increase the activity of the students.As for theformulaton of general problem of this study is whether the implementation of cooperative learning model NHT could improve the quality of science teaching five grade SDN 001 Seberida?. The purpose of this research is to improve the quality of learning include the teacher skills. Students activities and the result of give grade students learn science at SDN 001 Seberida. This type of the research is classroom action research with 2 cycles. Each cycle consist of four stage: Planning, implementation, Observation, and reflwction.The subject of this research is the teacher and students in 5 grade SDN 001 Seb erida. Data collection teachnigues using tests, observation, field notes, and dokumentation the results showed for the first cycle ofthe teacher skills to earn a score of 16 at the meeting of 1 and a score of 17 in the second sycle to obtain a score of 18 at the meeting of 1 and a score of 21 in the second meeting with criteria very well. Students activity cycle 1 scored 15 in the first meeting with sufficient criteria. Scond cycle increase a score of 18 at the meeting of 1 and a score of 20 in the second meeting with both criteria.Mastery Learning Classical, the first eycle is 60% the socond cycle increased to 72%. The conclusions of this study is teacher, activities, students, and student learning otcome class V SDN 001 Seberida in science subjects.Advice given that teacher should use inaovative models and verying media in Learning.Key word : Cooperative Learning Model Numbered Head Together (NHT), Learning outcomes.